(untitled) (Editora Impacto Científico, 2025)
This study proposes a sustainable and high-performance alternative to traditional fiber cement, addressing asbestos replacement and the valorization of industrial waste. The composite was developed through extrusion, incorporating micro/nanofibrils (MNFs) of Erythrina poeppigiana cellulose and alkaline residues (Dregs) from the pulp and paper industry. To mitigate the degradation of the lignocellulosic fibers, cured samples were submerged in an EVA copolymer solution, generating a protective polymeric surface coating. The optimized composite (EVA2) demonstrated superior physical-mechanical performance, achieving a Modulus of Rupture (MOR) of 8.7 MPa and a Modulus of Elasticity (MOE) greater than 4.9 GPa, in addition to a significant reduction of up to 36% in water absorption compared to the control. Scanning Electron Microscopy (SEM) analysis confirmed the role of EVA as a physical barrier, promoting greater matrix cohesion and lower interfacial porosity. The results confirm the technical and environmental feasibility for the production of an advanced fiber cement intended for the construction industry. DOI: https://doi.org/10.56238/edimpacto2025.090-076